The gluteal triangle: a clinical patho-anatomical approach to the diagnosis of gluteal pain in athletes. Issue 6 (19th November 2008) - Franklyn-Miller, A; Falvey, E; McCrory, P
Abstract : Gluteal pain is a common presentation in sports medicine. The aetiology of gluteal pain is varied, it may be referred from the lower back, mimic other pathology and refer to the hip or the groin. The complex anatomy of the buttock and pelvis, variability of presentation and non specific nature of signs and symptoms make the diagnostic process difficult. To date the approaches to this problem have focused on individual pathologies. The paper proposes a novel educational system based on patho-anatomic concepts. Anatomical reference points were selected to form a diagnostic triangle, which provides the discriminative power to restrict the differential diagnosis, and form the basis of ensuing investigation. This paper forms part of a series addressing the three dimensional nature of proximal lower limb pathology. The 3G approach (groin, gluteal and greater trochanter triangles) acknowledges this, permitting the clinician to move throughout the region, considering pathologies appropriately. These papers should be read in conjunction with one another in order to fully understand the conceptual approach.